ANALYSIS OF ADVERSE EVENTS REPORTED FOLLOWING SINGLE DOSE MONOVALENT H1N1 (SWINE FLU) VACCINE - Ahmed, Farooq; Rauf, Muhammad Abdul; Maula, Fazle; Mehmood, Nida (Journal of Postgraduate Medical Institute, 2012)
Objective: To identify the adverse events reported following monovalent single dose intramuscular SwineFlu Vaccine within a period of 6 weeks after vaccination. Methodology: This descriptive study was conducted from November 2010 to January 2011 in Lady ReadingHospital Peshawar, a 1400 bedded, tertiary care hospital, where single dose monovalent swine flu vaccinewas available free of cost. Recipients were all healthy hospital employees, above 18 years of age. Aprinted proforma was designed, in which adverse events were recorded (either by telephone or personalappearance) after 24 hours, 1 week and then after 6 weeks. Informed consent was taken before vaccineadministration. The study was approved by the ethical review committee of the institution. Results: Seven hundred and ninety two individuals were included in the study with mean age of 27.67(SD=10.7). Males were 52.3% while the rest were female. Two hundred and fifty (31.6%) were students,214 (27%) were paramedical staff, 153 (19.3%) were doctors, 139 (17.6%) were nursing staff, while 19(2.4%) were senior teaching staff. After 24 hours of vaccination, redness at injection site was found in 36(4.5%), soreness in 29 (3.7%), and itching in 23 (2.9%), headache in 66 (8.3%), nausea in 35 (4.4%),fever in 21 (2.7%), dizziness in 6 (0.8%), and muscle aches in 1 (0.1%). After 7 days, only 3 (0.4%)individuals had soreness and tenderness at injection site, 2 (0.3%) had fatigue, 4 (0.5%) had fever and 2(0.3%) had dizziness. After 6 weeks, no local or systemic adverse events were noted. Conclusion: swine flu vaccine causes minor local or systemic side-effects in the form of pain, headache,fever, and fatigue in the first 24 hours of administration, and is free of short term and serious adverseevents.